Tectonic structure and volcanic centers at the eastern edge of the aegean volcanic arc around Nisyros island - PAPANIKOLAOU, D.; NOMIKOU, P. (Bulletin of the Geological Society of Greece, 2001)
The recent volcanic activity at the eastern edge of the Aegean Volcanic Arc is limited within a neotectonic graben structure which is developed in an E-W general direction between the alpine basement of Kos Island to the north and the alpine basement of Tilos Island to the south. In between the boundary faults of the neotectonic graben there is an extended volcanic area comprising several individual volcanic centers, which penetrate through the thick post-alpine sedimentary deposits of the graben.